MESINIAGA TOWER: TRADISIONALITAS DALAM BALUTAN MODERNITAS (SEBUAH APRESIASI KARYA ARSITEKTUR) - Prajnawrdhi, Tri Anggraini (Jurnal Natah, 2004)
In this moment, the inovations of architecture designing are already grown at full speed. The brilliance ideas of architects to solve settlement problems, especially they have relation with shortage of land use, come people dilemas up. This paper describes a appreciation of architecture, bioclimatic architecture concept by Ken Yeang. He try to solve some of settlement problems in this time, especially in urban areas. This concept in modernity designing is inspirated from traditional building of South East Asian in generally. It is based on spatial designing, lighting, air conditioning, landscaping, form and element of building, and designing concepts. However, this paper appears the new paradigm in spectacular of architecture by Ken Yeang at Mesiniaga Tower in Kuala Lumpur, Malaysia. Finally, it will come the new paradigm of Indonesian architectural.